Cooperation between NRF2-mediated transcription and MDIG-dependent epigenetic modifications in arsenic-induced carcinogenesis and cancer stem cells. (November 2021) - Bi, Zhuoyue; Zhang, Qian; Fu, Yao; Seno, Akimasa; Wadgaonkar, Priya; Qiu, Yiran; Almutairy, Bandar; Xu, Liping; Zhang, Wenxuan; Thakur, Chitra; Chen, Fei
Abstract: Environmental exposure to arsenic, a well-established carcinogen linked to a number of human cancers, is a public health concern in many areas of the world. Despite extensive studies on the molecular mechanisms of arsenic-induced carcinogenesis, how initial cellular responses, such as activation of stress kinases and the generation of reactive oxygen species, converge to affect the transcriptional and/or epigenetic reprogramming required for the malignant transformation of normal cells or normal stem cells remains to be elucidated. In this review, we discuss some recent discoveries showing how the transcription factor NRF2 and an epigenetic regulator, MDIG, contribute to the arsenic-induced generation of cancer stem-like cells (CSCs) as determined by applying CRISPR-Cas9 gene editing and chromosome immunoprecipitation followed by DNA sequencing (ChIP-seq).